The Influence of Israel Health Insurance Law on the Negev Bedouin Population — A Survey Study - Mohammed Morad; Shifra Shvarts; Joav Merrick; Jeffrey Borkan (The Scientific World Journal, 2006)
The extension of universal health service insurance to national populations is a relatively new phenomenon. Since 1995, the Israeli National Health Insurance Law (NHIL) has provided universal health services to every resident, but the effect of this law on health and health services among minorities has not been examined sufficiently. The goals of this study were to track some of the first changes engendered by the NHIL among the Negev Bedouin Arabs to examine the effects of universal health care services. Methods included analysis of historical and health policy documents, three field appraisals of health care services (1994, 1995, 1999), a region-wide interview survey of Negev Bedouins (1997), and key informant interviews. For the interview survey, a sample of 515 households was chosen from different Bedouin localities representing major sedentarization stages. Results showed that prior to the NHIL, a substantial proportion of the Negev Bedouins were uninsured with limited, locally available health service. Since 1995, health services, particularly primary care clinics and health manpower, have dramatically expanded. The initial expansion appears to have been a marketing ploy, but real improvements have occurred. There was a high level of health service utilization among the Bedouins in the Negev, especially private medical services, hospitals, and night ambulatory medical services. The NHIL brought change to the structure of health services in Israel, namely the institution of a national health system based on proportional allocation of resources (based on size and age) and open competition in the provision of quality health care. The expansion of the pool of potential members engendered by the new universal coverage had profound effects on the Health Funds' attitudes towards Negev Bedouins. In addition, real consumer choice was introduced for the first time. Although all the health care needs of this rapidly growing population have yet to be met fully, the assurances under the Law and the new level of competition promise a higher level of service in the future.